PRAKTIK PENGANGKATAN ANAK DI KABUPATEN PACITAN: IMPLIKASI ADMINISTRASI KEPENDUDUKAN TERHADAP PERWALIAN NIKAH DALAM PERSPEKTIF FIQH MUNAKAHAT - Doni Isroyan; Izzul Mutho` (LPPM STAI Muhammadiyah Probolinggo, 2026)
This study analyzes child adoption practices in Pacitan Regency and its implications for marriage guardianship from a Fiqh Munakahat perspective. The primary focus is the administrative recording of adoptive parents' names in birth certificates, which potentially obscures a child's lineage (nasab). Through qualitative field research at the Pacitan Civil Registration Office, Religious Court, and Arjosari Religious Affairs Office, it was found that the Civil Registration Office employs a